MENINGKATKAN KETERAMPILAN DRIBBLING FUTSAL MELALUI METODE BERMAIN - Yandri Driyana Firmansah; Hernawan; Aan Wasan; Widiastuti (Jurnal Penjaskesrek, 2019)
This research was conducted to see the improvement of futsal dribbling skills at the MTs Daarul U'luum PUI Majalengka School through playing methods. This study uses Action Research method (action research). The penetlitian model of action used is the Kemmis and Mc model. Taggart with 4 processes, namely process (1) Planning, (2) Implementation of Action, (3) Observation or Observation, and (4) Reflection. This research was carried out at MTs Daarul U'luum PUI, Majalengka District, Majalengka District. The subjects of this study amounted to 30 students. The instrument used in this study is a test and observation instrument. The results of the assessment of futsal dribbling skills in the initial data were around 26% of students who achieved the KKM score. In Cycle I researchers applied a play method to improve futsal dribbling skills. The result is around 60% of students who achieve KKM scores. In the second cycle there is an increase in students who scored above the KKM approximately 83.33% of students. In this cycle is said to be successful because 80% of the number of students already meet the KKM. Results Performance Researchers in the first cycle, obtained a percentage of about 93.75, in cycle II, researchers get 100 percent. Student activity on the first cycle, earn a percentage 76,6% is quite good, while in cycle II, students' activities to increase with the percentage to 93.33% are very good. Thus it can be concluded that the method of play can improve the skills of futsal dribbling. Abstrak Penelitian ini dilakukan untuk melihat peningkatkan keterampilan dribbling futsal di Sekolah MTs Daarul U’luum PUI Majalengka melalui metode bermain. Penelitian ini menggunakan metode Action Research (penelitian tindakan). Model penetlitian tindakan yang digunakan adalah model Kemmis dan Mc. Taggart dengan 4 proses yaitu proses (1) Perencanaan, (2) Pelaksanaan Tindakan, (3) Observasi atau Pengamatan, dan (4) Refleksi.Penelitian ini dilaksanakan di MTs Daarul U’luum PUI Kecamatan Majalengka Kabupaten Majalengka.Subjek penelitian ini berjumlah 30 siswa.Instrument yang digunakan dalam penelitian ini adalah instrumen tes dan observasi.Hasil penilaian keterampilan dribbling futsal pada data awal sekitar 26% siswa yang mencapai nilai KKM.Pada Siklus I peneliti menerapkan metode bermain untuk meningkatkan keterampilan dribbling futsal.Hasilnya sekitar 60% siswa yang mencapai nilai KKM. Pada siklus II terdapat peningkatan siswa yang mendapat nilai di atas KKM sekitar 83,33% siswa. Pada siklus ini dikatakan berhasil dikarenakan sudah 80% dari jumlah siswa sudah memenuhi KKM..Hasil Kinerja Peneliti pada siklus I, memperoleh persentase sekitar 93,75, pada siklus II, peneliti memperoleh persentase 100. Hasil aktivitas siswa pada siklus I, memperoleh perentase 76,6% tergolong baik, sedangkan pada siklus II, aktivitas siswa memperoleh peningkatan dengan persentase menjadi 93,33% tergolong sangat baik. Dengan demikian dapat disimpulkan bahwa metode bermain dapat meningkatkan keterampilan dribbling futsal. Kata Kunci: bermain, keterampilan dribbling, futsal